ADVICE FROM A PROFESSIONAL: The DNA of a Technical Communicator - Nyberg, Mette (Communication & Language at Work, 2013)
Unlike our peers in the US or UK, the technical communicators in the Danish/Scandinavian region have not had the luck of easy access to formal education within the field of technical communication. I claim that most of us technical communicators in the Danish/Scandinavian region do not have a formal technical communication degree. We have learned on the job – spiced with relevant courses (such as Information Mapping), and we have kept ourselves up to date by attending conferences, reading books and articles. For the past 10 years or so we have been blessed with the growing wealth of information on the Internet to keep us in the loop and the social media to exchange views and experiences. This article discusses the evolution of a technical communicator profile as known in the Danish/Scandinavian region and what it takes to become a good technical communicator. What is indeed the skill set of a good technical communicator? Is there at all a future for technical communicators - and is it a promising career path?